Lewis and Clark Exposition Waltzes (Papinta waltzes) - Frieda Pauline Cohen::::::::: (Victor Kremer)
Cover title: Lewis and Clark exposition waltz. By Pauline Cohen. On cover is vignette of Lewis and Clark with allegorical figure of woman representing the U.S. walking toward the rising sun, by Raphael Beck, c1903 by Lewis and Clark Exposition Co., Same vignette on margin of each page of music. Also on cover: Respectfully dedicated to Mr. John A. Wakefield. Publishers advertisement on verso of last leaf.